ANALISA (MIS) MATCH TENAGA KERJA DI ASIA TENGGARA - Aning Kesuma Putri; Ratu Eva Febriani (Universitas Bengkulu, 2020)
The mismatch between jobs and skills indicates the match model in the job market is not going well, which is referred to as (e.g.) labor match, which leads to overeducation and undereducation in the job market. This research was conducted to find the influence of growth, overeducation and undereducation on wages in Southeast Asia. The data used is secondary data sourced from https://ilostat.ilo.org/data/ data in 2010-2019, especially in 8 Southeast Asian countries consisting of Brunai Darusalam, Philippines, Laos, Indonesia, Cambodia, Thailand, Timor Leste and Vietnam. The results found that the workers with the highest undereducated levels were in Timor Laste, then Laos and Cambodia. Worker conditions in developing countries such as Southeast Asia have more undereducation conditions than overeducation. Economic growth, overeducation and undereducatio affect workers' wages. Keywords: overeducation, undereducation, mismatch, labor